Estimated risks of recurrence and mortality in lung cancer: comprehensive analysis by a population-based study - Tanizaki, Junko; Hayashi, Hidetoshi; Nakagawa, Kazuhiko (Translational Cancer Research, 2017)
Lung cancer remains the leading cause of cancer-related mortality worldwide in spite of recent advances in treatment. Prognosis varies from patient to patient according to a variety of factors such as disease stage and treatment modality. Compared with those enrolled in clinical trials, which tend to be restrictive in their eligibility criteria, a greater variety of lung cancer patients is encountered in daily clinical practice. It would therefore be helpful for oncologists to be able to estimate the risks of disease recurrence as well as survival for patients in such a general population.